Vigilance, risk, and service use among caregivers of people living with dementia. (May 2023) - McCann, Brandy Renee; Roberto, Karen A; Blieszner, Rosemary; Savla, Jyoti; Atkinson, Emily
Objective: The purpose of this investigation was to understand the dynamics among dementia caregiving, vigilance, and home and community-based service use. Methods: This paper is derived from a larger, mixed-methods study on caregiving. We used a descriptive qualitative approach to analyze interview data of 30 family caregivers of relatives with dementia. Results: We found five domains of vigilance in which caregivers felt "on duty": ensuring attentiveness, ensuring safety, ensuring resources, ensuring healthcare, and ensuring closeness. Formal service use did not necessarily give caregivers relief from vigilance, with the language of risk often employed by caregivers. Conclusion: Because service use could contribute to feelings of vigilance, rather than give caregivers a break from a sense of watchfulness, these findings support calls for dementia-specific training for service providers. In future caregiving research, the relationship between vigilance, caregiver distress, and role captivity should be explored.